Comparisons of the genetic structure of Squalius populations (Teleostei, Cyprinidae) from rivers with contrasting histories, drainage areas and climatic conditions based on two molecular markers - Almada, Vítor Carvalho (2012)
The genetic structure of Squalius populations from Portuguese Atlantic- and Mediterranean-type streams (assigned to six distinct morphoclimatic regions) was compared using sequences of the cytb and betaactin genes. The drainage area was significantly correlated to all the genetic diversity indices, pointing to the need to control for this effect in comparing populations with different histories and paleoecologies. A significant correlation was also found between genetic diversity and the morphoclimatic regions to which the rivers were assigned, with the highest diversity in warmer, lower latitude, Mediterranean-type streams. This relationship was not due to idiosyncratic characteristics of the clades compared. When the drainage area and phylogenetic effects were removed, the southern Mediterranean streams harboured significantly more genetic diversity even when compared with much larger northern streams. It is argued that these results are likely caused both by the metapopulation structure of the Mediterranean streams and by the severe reduction or local extinction of populations in the northern rivers during glaciations.